Speech and Genre Characteristics of Express Consultation as a New Phenomenon of Medical Discourse - A. A. Kiselnikova (Дискурс, 2024)
Introduction. The aim of the article is to analyze an extramural express consultation as a genre of oral medical discourse. New telemedicine technologies expand the forms of communication, it results in transformation of the dialogue between a doctor and a patient when communicating online, which requires linguistic research.Methodology and sources. The article is based on the main theses of the theory of speech genres formulated by M.M. Bakhtin, T.A. Van Dijk, O.B. Sirotinina, T.V. Shmeleva and others. The author has taken the scientific works on the study of speech genres of oral medical discourse as the methodological basis of the analysis. This includes the works of V.V. Zhura, E.A. Ponomarenko, M.I. Barsukova and others. The study applies methods of linguistic analysis of recorded online consultations for speech-genre characteristics of express consultations.Results and discussion. The article gives a description of an express consultation, including the following parameters: communicative goal, utterance content, speech roles of communicators, linguistic embodiment of the genre. The author pays special attention to doctor's communicative style and gives its assessment in terms of achieving communicative and consequently professional success. The author also describes a speech-genre scenario of a medical online consultation and a chain of communicative moves in a doctor's speech.Conclusion. The study shows that doctor's every speech act is specified by a complex system of communicative targets, primarily related to informative goals (requesting information from the patient and providing information in the form of an explanation and recommendation) and therapy goals to maintain a patient's psychological and emotional well-being. Communicators' speech behavior is regulated by the institutional roles of «an agent» and «a client» of an institution, native speakers having their own invariants. The utterance content is specified by a patient's specific complaint and is organized in accordance with the stages of a medical consultation. The study concludes that genre competence as a part of communicative competence in the form of online communication is the most important professional tool of a consulting specialist.